The portrayal of bullying in The Kid Who Would Be King (2019) - Ferine Febriana (Passage: Journal of English Language and Literature, 2023)
Bullying is a pattern of negative behavior, not an occasional incident, which still occurs frequently in society. In most cases, bullying happens to children at school. As the issue has received much public attention, bullying is commonly featured in numerous literary works, one of which is in the children's film by Joe Cornish, The Kid Who Would Be King (2019). Through analysis under the framework of film theory by Bordwell and Thompson (2016) and Foucault's (1995) theoretical framework of power, the film portrayed bullying toward students in school through the film's cinematography, sound, and mise-en-scène. The imbalance of power between the bullies and the bullied is the main factor causing acts of bullying. It shows in the difference of individual aspects such as body sizes and social standings in school, which the bullies usually have the more advantageous aspect than the bullied. The advantageous aspect makes the bullies superior, giving them a chance to cause negative impacts on the bullied personalities intentionally. The negative impact of bullying can lower the bullied self-esteem, making them feel worthless as an individual. Since bullying is also a critical issue that needs to explore further, the researcher conducts a textual analysis study to provide references to readers about bullying in children's films and raise awareness about bullying against children in schools.